Media coverage of New Zealand's 2014 election campaign. (December 2015) - Boyd, Mark; Bahador, Babak
New Zealand's 2014 general election campaign was seen by many observers as out of the ordinary: it was variously described as 'weird', 'bizarre' and 'crazy'. However, did media coverage reflect the unusual nature of the actual campaign? This study's content analysis of that coverage reveals that the news media's concentration on 'non-policy' issues meant that much of it was dominated by alleged scandals, which were reported with a negative tone, and less space was devoted to policy. However, this does not indicate an extraordinary shift in New Zealand politics. Although seen by many as damaging to democracy and antithetical to a robust public sphere, these are now often features of the media-dominated 'modern' campaign.